1978
DOI: 10.1530/acta.0.0890070
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies on the Iodine Organification Defect of Pendred's Syndrome

Abstract: Biochemical studies were performed on the thyroid of a typical case of Pendred's syndrome who underwent total thyroidectomy. The patient, a euthyroid 14 year old female, presented congenital nerve deafness, goitre and impairment of thyroidal iodine organification. Thyroid peroxidase (TPO) activity was quantitatively normal. Using crude preparations, enzyme activity ranged from 176\p=n-\366 nmoles of I \ m= -\ \ x = r e q -\ incorporated (inc.) to tyrosine/g of tissue. Normal values are 220\p=n-\410 nmoles I\m=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Other studies performed in thyroid tissues from patients with congenital goiter and defective TPO have indicated that the Tg obtained from these tissues can be normally iodinated and has a normal coupling reaction in vitro when incubated with hog TPO. In tissues with defective TPO, as expected, little MIT or DIT is formed, with only traces of T3 or T4 (66). It is conceivable that some Tg might be iodinated, some with T3 and T4 formation due to some TPO activity.…”
Section: Biochemical Studiessupporting
confidence: 72%
See 2 more Smart Citations
“…Other studies performed in thyroid tissues from patients with congenital goiter and defective TPO have indicated that the Tg obtained from these tissues can be normally iodinated and has a normal coupling reaction in vitro when incubated with hog TPO. In tissues with defective TPO, as expected, little MIT or DIT is formed, with only traces of T3 or T4 (66). It is conceivable that some Tg might be iodinated, some with T3 and T4 formation due to some TPO activity.…”
Section: Biochemical Studiessupporting
confidence: 72%
“…In retrospect, however, we may assume that the majority of cases had a quantitative type of TPO defect. This conclusion is reached through comparison with other documented instances of quantitative TPO deficiency (57,59,64,66,70,75,78). Strong points favoring a clinical diagnosis of a quantitative defect are large goiters, a complete discharge of iodide following perchlorate, more than one sibling affected in the family, consanguinity, and severe hypothyroidism.…”
Section: Classificationmentioning
confidence: 82%
See 1 more Smart Citation
“…Quan titative and qualitative studies done on thyroid peroxi dase in patients with Pendred's syndrome have been nor mal [5], Mason et al [6] have demonstrated abnormalities of the messenger ribonucleic acid encoding the 3-prime region of thyroglobulin. The exact nature of the biochemi cal defect in Pendred's syndrome remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Morgans and Trotter in 1958 demonstrated a presumed specific enzymatic defect as the cause of goitre in this condition [17]. The thyroid defect has been shown to be a partial defect in iodine organification leading to the under production of thyroxine [18]. This triggers the secretion of thyroid stimulating hormone (TSH) which stimulates thyroid gland hyperplasia to compensate for the defect by maintaining the minimal level of thyroid hormones production to keep the patient euthyroid.…”
Section: Pathogenesismentioning
confidence: 99%